Individual lymph nodes: "See it and Zap it". (September 2019) - Winkel, Dennis; Werensteijn-Honingh, Anita M.; Kroon, Petra S.; Eppinga, Wietse S.C.; Bol, Gijsbert H.; Intven, Martijn P.W.; de Boer, Hans C.J.; Snoeren, Louk M.W.; Hes, Jochem; Raaymakers, Bas W.; Jürgenliemk-Schulz, Ina M.
Highlights: 10 patients with lymph node oligometastases received SBRT using a 1.5T MR-linac. Impact of planning strategies "adapt to shape" and "adapt to position" was compared. ATS resulted in a slightly better target coverage compared to ATP. A 3 mm isotropic GTV-PTV margin was adequate. "Seeing and Zapping" metastatic lymph nodes comes within reach for MRI-guided SBRT. Abstract: Background and purpose: With magnetic resonance imaging (MRI)-guided radiotherapy systems such as the 1.5T MR-linac the daily anatomy can be visualized before, during and after radiation delivery. With these treatment systems, seeing metastatic nodes with MRI and zapping them with stereotactic body radiotherapy (SBRT) comes into reach. The purpose of this study is to investigate different online treatment planning strategies and to determine the planning target volume (PTV) margin needed for adequate target coverage when treating lymph node oligometastases with SBRT on the 1.5T MR-linac. Materials and methods: Ten patients were treated for single pelvic or para-aortic lymph node metastases on the 1.5T MR-linac with a prescribed dose of 5x7Gy with a 3 mm isotropic GTV- PTV margin. Based on the daily MRI and actual contours, a completely new treatment plan was generated for each session (adapt to shape, ATS). These were compared with plans optimized on pre-treatment CT contours after correcting for the online target position (adapt to position, ATP). At the end of each treatment session, a post-radiation delivery MRI was acquired on which the GTV was delineated to evaluate the GTV coverage and PTV margins. Results: The median PTV V35Gy was 99.9% [90.7–100%] for the clinically delivered ATS plans compared to 93.6% [76.3–99.7%] when using ATP. The median GTV V35Gy during radiotherapy delivery was 100% [98–100%] on the online planning and post-delivery MRIs for ATS and 100% [93.9–100%] for ATP, respectively. The applied 3 mm isotropic PTV margin is considered adequate. Conclusion: For pelvic and para-aortic metastatic lymph nodes, online MRI-guided adaptive treatment planning results in adequate PTV and GTV coverage when taking the actual patient anatomy into account (ATS). Generally, GTV coverage remained adequate throughout the treatment session for both adaptive planning strategies. "Seeing and zapping" metastatic lymph nodes comes within reach for MRI-guided SBRT.